Analysis of the Conformity of Mudharabah Contracts in Suka-Suka Savings Products at Bank Mega Syariah KCP Medan Katamso - Rizky Ananda Utami; Mustopa Khamal Rokan (Journal of Indonesian Management, 2022)
Sharia banking is currently on the rise and has become a reference for the public to invest their funds for various needs. For this reason, various Islamic banking products must be able to be understood by the public, one of which is the application of mudharabah contracts on savings products. This article discusses the analysis of the suitability of the Mudharabah Agreement in the Suka-Suka Savings Products at Bank Mega Syariah KCP Medan Katamso. This article uses qualitative research with data collection through direct interviews with stakeholders at Bank Mega Syariah KCP Medan Katamso. The results of this study are the application of the contract used in the Suka-suka Savings is the mudharabah muthlaqah contract, which is a form of cooperation between the shahibul maal (the owner of the funds) namely the customer and the mudharib (the fund manager) namely the bank, where the owner of the funds (shahibul maal) does not provide restrictions on mudharib in determining the type of business, time and area of business as long as it does not conflict with sharia principles and is in accordance with bank regulations.